The Influence of Social Context on the Functionality of Family and the Development of Human Personality in Heinrich Böll’s Novel The Clown - Stipančević, Ana I. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
In every period there exist certain social, economic, and moral turmoil, it reflects within a family dynamic. The behavior of a family in times of crisis is an important indicator of the general condition and relations within that family. In such circumstances is when a family's power shows. Communities in which harmony and unity govern will in fact cope easier in critical situations, than those in which harmony and cohesiveness do not exist. Such a critical period was before and after the World War II, in which two different social systems, Nazism and democracy, determined the lifestyle and behavior of the Germans. The novel by H. Böll, The Clown, is placed in this timeframe and is used to study the influence of social context on the family dynamic. The paper will, among other things, determine the extent to which the Schnier family functioned, in terms of unity and strength to overcome the critical situation it was in. Apart from the influence of the social environment on the development of personality, family also has a significant role in shaping a person and their integration into the community, this will be studied along with the influence of these factors on the development of the main character’s personality, Hans Schnier.
Keywords: social context; family dynamic; development of human personality; Heinrich Böll